Răspuns:
a) \(a = (-2)-(-3)\), \(b = (-3) - (+4)\)
\[a = -2 + 3 = 1, \quad b = -3 - 4 = -7\]
Deoarece \(1 > -7\), avem \(a > b\).
b) \(a = (-5) - (+7)\), \(b = (-7) - (-5)\)
\[a = -5 - 7 = -12, \quad b = -7 + 5 = -2\]
Deoarece \(-12 < -2\), avem \(a < b\).
c) \(a = (-10) - (-10)\), \(b = (+10) - (-10)\)
\[a = -10 + 10 = 0, \quad b = 10 + 10 = 20\]
Deoarece \(0 < 20\), avem \(a < b\).
d) \(a = (-1)-(+3)\), \(b = (+2)-(-2)\)
\[a = -1 - 3 = -4, \quad b = 2 + 2 = 4\]
Deoarece \(-4 < 4\), avem \(a < b\).
e) \(a = (-5)-(-2)\), \(b =(+5)-(-2)\)
\[a = -5 + 2 = -3, \quad b = 5 + 2 = 7\]
Deoarece \(-3 < 7\), avem \(a < b\).
f) \(a = (-3) + (-2)\), \(b =(-3)-(+2)\)
\[a = -3 - 2 = -5, \quad b = -3 - 2 = -5\]
Deoarece \(-5 = -5\), avem \(a = b\).
Explicație pas cu pas:
Sper ca te am ajuns